2019
DOI: 10.2174/0929867326666190805153610
|View full text |Cite
|
Sign up to set email alerts
|

ADHD with Comorbid Bipolar Disorders: A Systematic Review of Neurobiological, Clinical and Pharmacological Aspects Across the Lifespan

Abstract: Background: Attention deficit hyperactivity (ADHD) disorder is a neurodevelopmental disorder characterized by inattention, hyperactivity, disruptive behaviour, and impulsivity. Despite considered typical of children for a long time, the persistence of ADHD symptoms in adulthood gained increasing interest during the last decades. Indeed, its diagnosis, albeit controversial, is rarely carried out even because ADHD is often comorbid with several other psychiatric diosrders, in particular with bipolar disorders (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 268 publications
0
10
0
Order By: Relevance
“…The identification of factors associated with comorbid ADHD could be useful to clarify if these subjects might represent a clinical subpopulation with specific unmet needs, thus requiring tailored treatments. In particular, we hypothesized that individuals with co-occurring BD and ADHD might be characterized by specific clinical features, for example, in terms of number of mood episodes, suicidal behaviors and additional comorbid conditions, such as anxiety and substance or alcohol use disorders (Bond et al, 2012; Hegerl et al, 2010; Klassen et al, 2010; Mucci et al, 2019; Sandstrom et al, 2021; Schiweck et al, 2021). To shed light on this topic, we performed a systematic review and meta-analysis of observational studies aimed at identifying sociodemographic and clinical correlates of ADHD among adults with BD and assessing the quality of existing evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of factors associated with comorbid ADHD could be useful to clarify if these subjects might represent a clinical subpopulation with specific unmet needs, thus requiring tailored treatments. In particular, we hypothesized that individuals with co-occurring BD and ADHD might be characterized by specific clinical features, for example, in terms of number of mood episodes, suicidal behaviors and additional comorbid conditions, such as anxiety and substance or alcohol use disorders (Bond et al, 2012; Hegerl et al, 2010; Klassen et al, 2010; Mucci et al, 2019; Sandstrom et al, 2021; Schiweck et al, 2021). To shed light on this topic, we performed a systematic review and meta-analysis of observational studies aimed at identifying sociodemographic and clinical correlates of ADHD among adults with BD and assessing the quality of existing evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of ADHD cases have comorbid mental health problems. Other studies have also observed a high level of comorbid mental illness among ADHD cases [7][8][9][10][11][12][13][14][15][16]. Because depression and anxiety are comparatively more common among the mental health problems, a higher percentage of ADHD cases had these comorbid conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Common comorbid problems associated with ADHD include autistic spectrum disorder (ASD), mania, schizophrenia, bipolar disorder, obsessive-compulsive disorder (OCD), depression, anxiety, learning disorders, sleep disorders, oppositional-defiant disorder (ODD), substance use disorders, and personality disorders [7][8][9][10][11][12][13][14]. A systematic review of the literature from 2019 found that bipolar disorder is a common comorbid condition for ADHD, with overlapping symptoms and complex treatment [15].…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar disorders (BDs) are psychiatric conditions characterized by mood, psychomotricity, and biorhythmicity disturbances. Bipolar disorder of type I (BDI) and of type II (BDII) represent the most severe types of BDs: the first is characterized by alternating depressive and manic episodes of great severity that frequently require hospitalization, while the second by depressive and hypomanic episodes . Currently, the debate concerning whether BDs should be primarily regarded as developmental or a neurodegenerative disorders is still open, although the two hypotheses do not appear necessarily mutually exclusive .…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar disorder of type I (BDI) and of type II (BDII) represent the most severe types of BDs: the first is characterized by alternating depressive and manic episodes of great severity that frequently require hospitalization, while the second by depressive and hypomanic episodes. 1 Currently, the debate concerning whether BDs should be primarily regarded as developmental or a neurodegenerative disorders is still open, although the two hypotheses do not appear necessarily mutually exclusive. 2,3 Indeed, postmortem studies highlighted different neuropathological abnormalities of glial and neuronal cells (in particular a loss of oligodendrocytes), albeit these alterations appear more limited than those observed in major neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%